CSR and Poverty Alleviation in Indonesia - Hasan, Annisa (2016)
There are a shifting role and responsibility of business in the globalization era beyond their economic role. In developing countries context, the private sector and their CSR activities started to be seen as the liberator of underdeveloped economies (Blowfield, 2005). Development agencies have come to see CSR as a way of reconciling support for private enterprise and a market-based system with their central aim of reducing global poverty (Jenkins, 2005). Poverty is one of the most prominent issues that needs to be tackled in the developing countries. Indonesia, as one of the developing country, is still struggling with the poverty issue. The Indonesian Government considers business as an important stakeholder in the development. This is indicated by the establishment of several policies on mandatory CSR for every company in Indonesia. This research aim to identify CSR approach, role, partner, challenge and strategy used by 10 biggest corporations (listed in the LQ45 index) in Indonesia in conducting poverty alleviation. The result identify economic contribution and social development approach of the conduction of poverty alleviation.